“El Entierro de la Sardina” and Sustainable Tourism: Evaluation of its Cultural Management Model - Zerpa Pérez, Rosabel (2018)
The investigation evaluates the cultural management model of the traditional festival of Naiguatá called “Entierro de la Sardina” in Venezuela and its relationship with the sustainable development of tourism. The research is a mixed nature one, and started from the understanding of the manifestation as a space of particular symbolic consumption in order to study the cultural management model that allows it to remain active. The DOFA Matrix was used in the diagnosis and it was concluded that the festival, as an attraction with cultural values, could promote economic development, preserve the heritage from a sustainable perspective.